Blues Mandolin Man : The Life and Music of Yank Rachell - Congress, Richard (Book collections on Project MUSE., 2001)
Yank Rachell and his mandolin playing style moved every musician lucky enough to hear him perform in the early sixties. When he died in April 1997, he left behind a stack of unanswered requests to tour Europe and to play blues festivals in the United States. In Blues Mandolin Man: The Life and Music of Yank Rachell, Richard Congress delivers the first biography of a family man whose playing inspired and energized the likes of David Honeyboy Edwards, Sleepy John Estes, and Henry Townsend. No other biography discusses the mandolin's influence and role in the blues. Guitar great Ry Cooder said, "